Pressure injury prevention: A scoping review of nurses’ knowledge, attitudes, and practices. - Shahadan , Siti Zuhaidah; Wan Mohd Amizi, Wan Nur Faqihah; Mohamad Ismail , Mohamad Firdaus (Journal of Islamic, Social, Economics and Development, 2025)
Pressure injuries are a significant concern in healthcare settings, impacting patient outcomes and quality of care. Nurses play a crucial role in preventing these injuries, yet knowledge, attitudes, and practices (KAP) among nurses remain inconsistent globally. This scoping review examines the levels of knowledge, attitudes, and practices related to pressure injury prevention among nurses and identifies influencing factors. A systematic search of scholarly articles was conducted using ProQuest Health & Medical Complete and ScienceDirect databases, complemented by a manual search of reference lists. Inclusion criteria were studies published within the past five years, available in English, and focused on KAP related to pressure injury prevention among nurses. The PRISMA framework guided the selection of 22 studies for this review. Studies demonstrated variability in KAP levels, with gaps noted in the knowledge of pressure injury aetiology, classification, and prevention strategies. Positive attitudes toward prevention were associated with training, education, and experience. Practices varied, with higher levels observed among critical care nurses and those with access to updated guidelines. Regional differences highlighted the need for targeted interventions in low-resource settings. The findings emphasize the need for standardized training programs, evidence-based guidelines, and policy initiatives to enhance nurses' KAP in pressure injury prevention. Future research should validate the developed KAP framework and assess its effectiveness in clinical settings.